Determination of saturates, aromatics and ethanol in Brazilian commercial gasoline with low olefin content using 1 H NMR spectroscopy - de Oliveira Ferreira, Fabrício [UNESP]; Flumignan, Danilo Luiz [UNESP]; Lopes, Márcia Nasser [UNESP]; Flumignan, Ermelindo; de Oliveira, José Eduardo [UNESP] (My University, 2010)
In this work, a Hydrogen Nuclear Magnetic Resonance (1H NMR) method has been developed to determine aromatics and ethanol in Brazilian commercial gasoline with low olefin content. The proposed method involves subdividing an 1H NMR spectrum into regions, each of which is assumed to be associated with a specific type of structural group (OH, CH, CH2 and CH3). The method is based on the assignment of overlapping regions of 1H NMR spectra due to the signals of naphthene (N), iso and normal paraffins (P) and ethanol (E). Each 1H NMR spectrum was divided into 8 regions and the integration was correlated to the percentage of the substances to be determined. The results of the analysis by 1H NMR were compared with analysis of GC-FID obtained with the PONA system. The proposed technique of 1H NMR was shown to be an appropriate method for this sample type.
Keywords: 1H NMR spectroscopy; Commercial gasoline; Ethanol